Staging Rachel : Rabbinic Midrash, Theatrical Mime, and Christian Martyrdom in Late Antiquity - Hadjittofi, Fotini (2021)
Lamentations Rabbah Proem 24, a late ancient rabbinic midrash, is in many ways a unique text within the entire rabbinic corpus. It presents an extraordinary array of characters (including Abraham, Moses, the Torah, and even the alphabet) who are called upon to placate God, but fail. As their quest proves inconclusive, the biblical Rachel jumps into the fray to tell her story: how out of sisterly compassion she allowed Leah to take her own place in the conjugal bed on “her” wedding night. Disclosing to her sister the secretive “signs” she had shared with Jacob, Rachel crawled under the nuptial bed to respond to Jacob whenever he spoke. This scandalous autobiography transforms an apparent instance of illicit sex, the ideal material for theatrical stage mimes, into an act of martyrdom and sublime compassion. This article argues that the performance culture of the late ancient Mediterranean world provides the key for assessing this text’s originality. We begin with an analysis of the text, drawing attention to its theatrical qualities and its relationships with contemporary visual imagery (mosaics) and texts from outside the rabbinic milieu (Christian Apocrypha). We then examine the casting of midrashic Rachel as a response to both the mimic adulteress and the Christian martyr. Finally, we consider rabbinic familiarity with mime, particularly with its usefulness as a social mediator and agent of collective catharsis. It is precisely these aspects of mimic performance, we argue, that Rachel’s vignette appropriates in this fascinating rabbinic text.